The effect of SSRIs on Semen quality: A systematic review and meta-analysis - Xu, Jiarong; He, Kancheng; Zhou, Yihong; Zhao, Liangyu; Lin, Yuteng; Huang, Zihao; Xie, Nengqing; Yue, Jihui; Tang, Yuxin (Frontiers in Pharmacology, 2022)
Selective serotonin reuptake inhibitors (SSRIs) are widely used for a variety of diseases, and their impact on semen quality is unclear. We performed a systematic search in PubMed and Embase, and after a strict screening, we included 4 studies with a total of 222 male participants. In result, SSRIs reduced normal sperm morphology (95% CI[-16.29, -3.77], p=0.002), sperm concentration (95%CI[-43.88, -4.18], p=0.02), sperm motility (95%CI[-23.46, -0.47], p=0.04) and sperm DNA fragmentation index (DFI)(95% CI[6.66,21.93], p=0.0002), without a statistically significant effect on semen volume (95%CI [-0.75,0.65], p=0.89). Moreover, the impact on both sperm morphology and sperm concentration were observed within the 3-month period of SSRI use. Our meta-analysis showed that SSRIs have a negative effect on semen quality, so we recommend that males of reproductive age temporarily consider not conceiving while using SSRIs. More larger, randomized, well-controlled clinical studies should be conducted to support our conclusion.